1992
DOI: 10.1111/j.1471-0528.1992.tb14409.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against a pathogenetic role for endothelin in pre‐eclampsia

Abstract: Objective To assess whether increased placental or systemic endothelin synthesis has a pathogenic role in pre‐eclampsia (gestational proteinuric hypertension). Design Prospective observations study. Subjects 19 women with pre‐eclampsia and 10 healthy pregnant women were studied. All were in the last trimester. Main outcome measures Preproendothelin‐1 gene expression by Northern blot analysis and generation of endothelin‐1 precursor, big‐endothelin‐1, and endothelin isoforms, namely endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 29 publications
2
25
1
Order By: Relevance
“…The role of ET in pre-eclampsia is unclear, however, as contradictory reports exist concerning circulating ET levels in normotensive patients and those exhibiting this condition. Some reports have shown that prepro-ET-1 gene expression and plasma ET-1 levels are similar in both normal pregnancy and pre-eclampsia (Benigni et al, 1992;Otani et al, 1991), whilst others have reported elevated maternal plasma ET-1 levels in pre-eclampsia implicating ET in the impaired renal function and placental blood flow associated with the disease (Mastrogiannis et al, 1991;Nova et al, 1991;Clark et al, 1992). In the present study, we were unable to detect a difference in either the relative density or proportion of vascular and villous ET receptor imating the equilibrium dissociation constant from saturation data obtained under these conditions was therefore considered inappropriate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of ET in pre-eclampsia is unclear, however, as contradictory reports exist concerning circulating ET levels in normotensive patients and those exhibiting this condition. Some reports have shown that prepro-ET-1 gene expression and plasma ET-1 levels are similar in both normal pregnancy and pre-eclampsia (Benigni et al, 1992;Otani et al, 1991), whilst others have reported elevated maternal plasma ET-1 levels in pre-eclampsia implicating ET in the impaired renal function and placental blood flow associated with the disease (Mastrogiannis et al, 1991;Nova et al, 1991;Clark et al, 1992). In the present study, we were unable to detect a difference in either the relative density or proportion of vascular and villous ET receptor imating the equilibrium dissociation constant from saturation data obtained under these conditions was therefore considered inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating ET levels have been shown to increase during pregnancy and labour (Mastrogiannis et al, 1991); however, conflicting evidence exists concerning the possible role of ET in the pathogenesis of pre-eclampsia. While some reports have indicated a further elevation of plasma ET levels in this condition (Nova et al, 1991;Clark et al, 1992), more recent studies have not found a significant difference in plasma ET levels between pre-eclamptic and normal pregnancies (Benigni et al, 1992) nor any correlation between plasma ET-1 concentration, blood pressure or renal function during toxaemic pregnancy (Otani et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…11 Whether increased synthesis of endothelin occurs within the kidney during preeclampsia remains unknown, inasmuch as some studies have found a decrease in urinary excretion of endothelin, a measure of local renal synthesis, in preeclamptic women compared with normotensive pregnant women. 12,13 We recently reported that chronic reduced uterine perfusion pressure (RUPP) in pregnant rats resulted in significant elevations in MAP and reductions in kidney function. 14 Because the kidneys play a major role in the long-term regulation of arterial pressure, the first aim of the present study was to determine whether increases in renal preproendothelin mRNA expression were associated with the hypertension produced by chronic RUPP in pregnant rats.…”
mentioning
confidence: 99%
“…Plasma concentration of ET-1 has been measured in normal pregnant and preeclamptic women (12). Some, but not all, investigators have found higher ET-1 plasma concentrations of approximately two-to threefold in women with preeclampsia (12,15) Typically, plasma levels of ET-1 are highest during the latter stage of the disease, suggesting that ET-1 may not be involved in the initiation of preeclampsia, but rather in the progression of disease into a malignant phase. Although the elevation in plasma levels of ET-1 during preeclampsia is only two or threefold above normal, previous studies have reported that this level of plasma ET-1 can have significant long-term effects on systemic hemodynamics and arterial pressure regulation (16) Thus long-term elevations in plasma levels of ET-1 comparable to those measured in women with preeclampsia could play a role in mediating the reductions in renal function and elevations in arterial pressure observed in women with preeclampsia.…”
Section: The Endothelin System In Preeclamptic Womenmentioning
confidence: 99%